Prevalence and Correlates of Bipolar Disorder among Patients Attending Mental Health Services in Balochistan - Zain Ullah Khan, Zarmina Tareen, Ali Ehsan Mufti, Shams Ullah Bazai, Raz Muhammad Kakar, Ghulam Rasool, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Bipolar disorder (BD) is a chronic, severe mental illness marked by recurrent episodes of mania and depression. Despite its growing global burden, limited data exists on its prevalence and risk factors in under-researched regions such as Balochistan, Pakistan. Objective: To determine the prevalence and associated sociodemographic and clinical correlates of bipolar disorder. Methodology: This cross-sectional, quantitative study was conducted in four major psychiatric facilities in Balochistan. Four hundred patients were recruited using systematic random sampling. Diagnoses were confirmed using the DSM-5 criteria, and structured questionnaires were used to gather sociodemographic and clinical information. Results: The prevalence of bipolar disorder was found to be 18.5% among the studied population. Significant correlates included family history of mood disorders (OR=2.45, p=0.004), substance use (OR=1.88, p=0.017), un-employment (OR=1.61, p=0.031), and early age at onset (OR=2.92, p<0.001). Conclusion: Bipolar disorder is notably prevalent among psychiatric patients in Balochistan. Socioeconomic and clinical factors play a significant role in its occurrence. These findings highlight the need for targeted screening and mental health policy reforms in the region. Keywords: Bipolar disorder, Prevalence, Correlates, Psychiatric epidemiology, Risk factors